Lvov poetry school: history and poetic manner - Морина, Валерия (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2013)
The main purpose of this article is to present the scientific community of the Lvov poetry school and to describe its history, members and the main concepts of their poetic manner.